2013
DOI: 10.1007/s00394-013-0567-x
|View full text |Cite
|
Sign up to set email alerts
|

Higher body fatness in intrauterine growth retarded juvenile pigs is associated with lower fat and higher carbohydrate oxidation during ad libitum and restricted feeding

Abstract: Purpose A thrifty energy metabolism has been suggested in intrauterine growth restricted (IUGR) offspring. We characterized energy metabolism and substrate oxidation patterns in IUGR pigs in response to food restriction (FR) and refeeding (RFD).MethodsFemale pigs with low (L; 1.1 kg; n = 20) or normal birth weight (N; 1.5 kg; n = 24) were fed ad libitum after weaning. Half of L and N pigs were food restricted (R; LR, NR) from days 80 to 100 (57 % of ad libitum) and refeed from days 101 to 131, while the remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…In addition, increasing litter sizes in modern swine production have led to higher rates of piglets born with a low birth weight (LBW) [3]. Both newborn LBW human [46] and LBW piglets [710] seem to have a lower capacity to mount an antioxidant response. Newborns transitioning from maternal mediated respiration to autonomous pulmonary respiration outside the uterus are suddenly exposed to O 2 -derived free radicals [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, increasing litter sizes in modern swine production have led to higher rates of piglets born with a low birth weight (LBW) [3]. Both newborn LBW human [46] and LBW piglets [710] seem to have a lower capacity to mount an antioxidant response. Newborns transitioning from maternal mediated respiration to autonomous pulmonary respiration outside the uterus are suddenly exposed to O 2 -derived free radicals [11].…”
Section: Introductionmentioning
confidence: 99%
“…A redox imbalance affects cellular signaling, protein synthesis, and enhances proteolysis that can ultimately lead to a dysfunctional intestinal barrier and suboptimal regenerative potential as shown in vitro [1215]. Consequently, the observed redox imbalance and the downstream effects could explain the abnormal absorption and metabolism of nutrients, reduced growth and impaired development of the small intestine, liver, and muscle observed in LBW piglets [10, 16–21]. This redox imbalance appears to persist beyond weaning [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, palmitoleic acid and myristoleic acid were significantly high after an overnight fast compared to levels 4 or 8 hr after feeding. A series of studies have reported a similar effect of feed restriction and fasting on lipid metabolism (Krueger et al, 2013). This is a strategy to save glucose and proteins that are crucial fuels for some important organs (Lomb, Laurent, & Haigis, 2010).…”
Section: Fatty Acid Metabolismmentioning
confidence: 98%
“…Krueger et al. () reported that after feeding, growing pigs showed higher carbohydrate oxidation, whereas fat oxidation markedly decreased and then switched to fat synthesis. However, the physiological and biochemical response to ingestion and absorption of a diet are an inherently complicated process (Jones, Park, & Ziegler, ; Pellis et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation